Secukinumab after first-line tumor necrosis factor-alpha inhibitor therapy in psoriatic arthritis: A real-world retrospective cohort study - Tumay Ak; Leyla Mustafayeva; Ali Yagiz Ayla; Yeliz Celik; Gunay Can; Serdal Ugurlu (Archives of Rheumatology, 2024)
Objectives: This study compared the secukinumab treatment responses and adverse effects in psoriatic arthritis patients who received secukinumab as second-line with those that received secukinumab after two or more tumor necrosis factor-alpha (TNF-α) inhibitors. Patients and methods: The retrospective study included 68 psoriatic arthritis patients followed up between October 2018 and October 2021. The patients were divided into two groups according to their anti-TNF-α treatment history. Group 1 consisted of 29 patients (11 males, 18 females; mean age: 45.3±13.3 years; range, 21 to 69 years) who had previously received one anti-TNF-α agent, while Group 2 included 39 patients (18 males, 21 females; mean age: 46.4±13.0 years; range, 24 to 70 years) who had been treated with two or more anti-TNF-α agents. Treatment responses of the groups were measured and compared using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Visual Analog Scale (VAS). A posttreatment BASDAI score ≤4 was used as a criterion for remission. Results: The mean duration of secukinumab treatment was 16.6±12.7 months for Group 1 and 16.0±11.6 months for Group 2 (p=0.84). Both groups responded significantly to secukinumab in terms of BASDAI and VAS scores (p<0.001 and p<0.001, respectively). Group 1 had a greater decline in BASDAI and VAS scores than Group 2 (p=0.045 and p=0.032, respectively). Furthermore, the remission rate was greater in Group 1 compared to Group 2 (58% vs. 34%, p=0.03). The adverse effects of secukinumab treatment were an allergic reaction in Group 1 and one case of ulcerative colitis in Group 2. Conclusion: Second-line secukinumab treatment resulted in a greater decline in BASDAI and VAS scores. Moreover, secukinumab achieved a significantly higher rate of remission when it was used as second-line therapy after one anti-TNF-α agent.